Integration of STEAM Chemistry Learning Based on Local Wisdom to Strengthen Students’ Vocational Skills and Science Literacy: A Systematic Literature Review (2020–2025) - Winna Wijayati; Widiyanti Widiyanti; Yoto Yoto (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This Systematic Literature Review (SLR) study aims to analyze the trends, models, and effects of STEAM Chemistry Learning Based on Local Wisdom in strengthening students’ vocational skills and science literacy during the period 2020–2025. A total of 13 articles that met the inclusion criteria were reviewed from the Google Scholar database using the PRISMA 2020 Statement guidelines. The results of the review indicate an increasing trend toward interdisciplinary approaches that integrate science, technology, engineering, arts, and mathematics with cultural contexts and local community life. The most dominant models applied were Project-Based STEAM Learning (PjBL-STEAM) and Problem-Based Local Wisdom STEAM (PBLW-STEAM), which were shown to be effective in developing students’ creativity, collaboration, and problem-solving abilities. The integration of local wisdom not only made chemistry learning more contextual but also strengthened vocational competencies through practical and sustainable application